Efektivitas Layanan Bimbingan Kelompok Teknik Talking Stick Terhadap Manajemen Waktu Siswa Kelas VIII SMP Teuku Umar Semarang Tahun Ajaran 2023/2024 - Sabrina Williadana; Heri Saptadi Ismanto; G. Rohastono Ajie (Journal on Education, 2024)
Teuku Umar Middle School in Semarang has children who struggle with time problems, especially time management. The AKPD results for class VIII Teuku Umar Middle School Semarang show that most students have difficulty managing their time between academic and extracurricular activities well. These students usually do not submit their assignments on time and only prepare for the exams. This research aims to find out how well the talking stick approach group guidance service improves students' time management abilities. This research uses a real experimental research methodology with a quantitative research design. There were 104 students in the research sample. A total of twenty-two Class VIII-1 students took part in the trial. This study chose class VIII-3 as a sample using a cluster random sampling technique. It was determined that 25% of the total population would be the sample size. The research conclusion shows that the 2-tailed significance value is 0.012, which is below the cutoff limit of 0.05. This shows that there is a significant difference between the pre-test and post-test variables which supports Ha being accepted and Ho being rejected. The hypothesis "There is an influence between group guidance services on time management of 8th grade students of Teuku Umar Junior High School Semarang Learning Year 2023/2024" is accepted.